Adapting and Validating a Scale to Measure Sexual Stigma among Lesbian, Bisexual and Queer Women - Logie, Carmen H.; Earnshaw, Valerie (PloS one, 2015)
Lesbian, bisexual and queer (LBQ) women experience pervasive sexual stigma that harms wellbeing. Stigma is a multi-dimensional construct and includes perceived stigma, awareness of negative attitudes towards one's group, and enacted stigma, overt experiences of discrimination. Despite its complexity, sexual stigma research has generally explored singular forms of sexual stigma among LBQ women. The study objective was to develop a scale to assess perceived and enacted sexual stigma among LBQ women. We adapted a sexual stigma scale for use with LBQ women. The validation process involved 3 phases. First, we held a focus group where we engaged a purposively selected group of key informants in cognitive interviewing techniques to modify the survey items to enhance relevance to LBQ women. Second, we implemented an internet-based, cross-sectional survey with LBQ women (n=466) in Toronto, Canada. Third, we administered an internet-based survey at baseline and 6-week follow-up with LBQ women in Toronto (n=24) and Calgary (n=20). We conducted an exploratory factor analysis using principal components analysis and descriptive statistics to explore health and demographic correlates of the sexual stigma scale. Analyses yielded one scale with two factors: perceived and enacted sexual stigma. The total scale and subscales demonstrated adequate internal reliability (total scale alpha coefficient: 0.78; perceived sub-scale: 0.70; enacted sub-scale: 0.72), test-retest reliability, and construct validity. Perceived and enacted sexual stigma were associated with higher rates of depressive symptoms and lower self-esteem, social support, and self-rated health scores. Results suggest this sexual stigma scale adapted for LBQ women has good psychometric properties and addresses enacted and perceived stigma dimensions. The overwhelming majority of participants reported experiences of perceived sexual stigma. This underscores the importance of moving beyond a singular focus on discrimination to explore perceptions of social judgment, negative attitudes and social norms.